2020
DOI: 10.1016/j.xkme.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis and Mortality, Kidney Transplant, and Transition to Hemodialysis: Trends From 1996-2015 in the United States

Abstract: Rationale & Objective Transitions between dialysis modalities can be disruptive to care. Our goals were to evaluate rates of transition from peritoneal dialysis (PD) to in-center hemodialysis (HD), mortality, and transplantation among incident PD patients in the US Renal Data System from 1996 to 2015 and identify factors associated with these outcomes. Study Design Observational registry-based retrospective cohort study. Setting & Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Assisted PD was associated with a higher risk of death and a lower risk of transfer to HD. Similar findings have been described previously [14, 21, 25]. No temporal trends of the impact of assistance on patient and technique survival were observed in our study; this impact remained stable over time.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Assisted PD was associated with a higher risk of death and a lower risk of transfer to HD. Similar findings have been described previously [14, 21, 25]. No temporal trends of the impact of assistance on patient and technique survival were observed in our study; this impact remained stable over time.…”
Section: Discussionsupporting
confidence: 92%
“…Perl et al [26] observed an improvement in PD patient survival between 1995 and 2009 but only small changes in PD technique survival. More recently, Sukul et al [25] reported an increase in technique survival between 1996 and 2011, since the rates of death and transition to HD declined over this time period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations